ANALISIS PEMAHAMAN KONSEP MATEMATIS SISWA DITINJAU DARI TINGKAT KECEMASAN SISWA SMP N 3 AMONNGEDO - Salmawati; Desak Nyoman Sri Devi (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to analyze students' understanding of mathematical concepts in terms of their levels of math anxiety. The subjects of this research were eighth-grade students of SMP Negeri 3 Amonggedo. The respondents consisted of six students categorized into three levels of anxiety: high, moderate, and low. This research employed a qualitative analytical approach. Data were collected through a math anxiety questionnaire, a conceptual understanding test, and in-depth interviews. Data analysis was conducted by examining five indicators of conceptual understanding in mathematics, namely solving problems in a structured manner, relating problems to variables, applying problem-solving methods, performing algorithmic calculations, and validating the correctness of answers. The results showed differences in students' conceptual understanding according to their level of anxiety. Students with low levels of anxiety demonstrated high levels of understanding, as indicated by structured solutions, correct method application, and confidence in drawing conclusions. Students with moderate anxiety showed a moderate level of understanding, with the ability to plan strategies but still experienced technical errors and uncertainty. Meanwhile, students with high anxiety levels exhibited low understanding, characterized by indecision in choosing steps, difficulty applying methods, and lack of confidence in their solutions. These findings indicate that math anxiety levels affect the quality of students' conceptual understanding in mathematics.